Gleason pattern 5 is the strongest pathologic predictor of recurrence, metastasis, and prostate cancer–specific death in patients receiving salvage radiation therapy following radical prostatectomy. Issue 18 (2nd July 2013) - Jackson, William; Hamstra, Daniel A.; Johnson, Skyler; Zhou, Jessica; Foster, Benjamin; Foster, Corey; Li, Darren; Song, Yeohan; Palapattu, Ganesh S.; Kunju, Lakshmi P.; Mehra, Rohit; Feng, Felix Y.
<x xml:space="preserve">Abstract</x> BACKGROUND The presence of Gleason pattern 5 (GP5) at radical prostatectomy (RP) has been associated with worse clinical outcome; however, this pathologic variable has not been assessed in patients receiving salvage radiation therapy (SRT) after a rising prostate‐specific antigen level. METHODS A total of 575 patients who underwent primary RP for localized prostate cancer and subsequently received SRT at a tertiary medical institution were reviewed retrospectively. Primary outcomes of interest were biochemical failure (BF), distant metastasis (DM), and prostate cancer–specific mortality (PCSM), which were assessed via univariate analysis and Fine and Grays competing risks multivariate models. RESULTS On pathologic evaluation, 563 (98%) patients had a documented Gleason score (GS). The median follow‐up post‐SRT was 56.7 months. A total of 60 (10.7%) patients had primary, secondary, or tertiary GP5. On univariate analysis, the presence of GP5 was prognostic for BF (hazard ratio [HR] 3.3; P < .0001), DM (HR:11.1, P < .0001), and PCSM (HR:8.8, P < .0001). Restratification of the Gleason score to include GP5 as a distinct entity resulted in improved prognostic capability. Patients with GP5 had clinically worse outcomes than patients with GS8(4+4). On multivariate analysis, the presence of GP5 was the most adverse pathologic predictor of BF (HR 2.9; P < .0001), DM (HR 14.8; P < .0001), and PCSM (HR 5.7; P < .0001). CONCLUSION In the setting of SRT for prostate cancer, the presence of GP5 is a critical pathologic predictor of BF, DM, and PCSM. Traditional GS risk stratification fails to fully utilize the prognostic capabilities of individual Gleason patterns among men receiving SRT post‐RP. Cancer 2013;119:3287–94. © 2013 American Cancer Society.